Water energy food security nexus: perspectives and challenges in Balochistan, Pakistan. (29th July 2022) - Gul, Warda; Makki, Muhammad; Yamin, Tughral
This paper utilises the autoregressive distributive lag model to examine the interrelationship between the overall water availability in Pakistan with HDI to uncover the correlation between water insecurity and the standard of living. The paper encapsulates the implications of the water energy food nexus and its challenges in identifying the role water security plays in food and energy production. This analysis helps understand the non-traditional security threats in Balochistan's case under the combined umbrella of the WEF nexus. It further uncovers the different causes of water scarcity in Balochistan and helps understand the role of water property rights. Findings report several projected WEF challenges: inequitable distribution of resources, shortage of dams, poor policy-making and low precipitation. Finally, coupled with high inflation and inadequate distribution of food resources within different regions of Balochistan, this paper reiterates the significance of the nexus and interconnects the WEF insecurities under one paradigm.